Lactobacillus paracasei ATG-E1 improves particulate matter 10 plus diesel exhaust particles (PM10D)-induced airway inflammation by regulating immune responses - Lee, Young-Sil; Park, Gun-Seok; Ko, Seung-Hyun; Yang, Won-Kyung; Seo, Hye-Jin; Kim, Seung-Hyung; Jeong, Nara; Kang, Jihee (Frontiers in Microbiology, 2023)
Particulate matter (PM) exposure can adversely affect respiratory function. Probiotics can alleviate the inflammatory responses in respiratory diseases. We examined the protective effects of Lactobacillus paracasei ATG-E1 isolated from the feces of a newborn baby against airway inflammation in a PM plus diesel exhaust particle (DEP) (PM10D)-induced airway inflammation model. BALB/c mice were exposed to PM10D by intranasal tracheal injection three times at 3-day intervals for 12 days, and L. paracasei ATG-E1 was administered orally for 12 days. Immune cell subtype analyses and expression of various inflammatory mediators and gut barrier-related genes were determined in bronchoalveolar lavage fluid (BALF), lung, Peyer’s patch, and small intestine. A histological analysis of the lungs was performed. In addition, the in vitro safety and their safety in genomic analyses were examined. L. paracasei ATG-E1 was found to be safe in vitro and by genomic analysis. L. paracasei ATG-E1 suppressed neutrophil infiltration and the number of CD4+, CD4+CD69+, CD62L-CD44+high, CD21/35+B220+, and Gr-1+CD11b+ cells, as well as the expression of cytokines and chemokines, including chemokine (C-X-C motif) ligand (CXCL)-1, macrophage inflammatory protein (MIP)-2, interleukin (IL)-17a, tumor necrosis factor (TNF)-α, and IL-6 in BALF and lungs in PM10D-induced airway inflammation. It protected against histopathological damage in the lungs of mice with PM10D-induced airway inflammation. L. paracasei ATG-E1 concomitantly increased the expression levels of the gut barrier function-related genes occludin, claudin-1, and IL-10 in the small intestine, with an increased number of CD4+ and CD4+CD25+ immune cells in the Peyer’s patch. L. paracasei ATG-E1 suppressed immune activation and airway inflammatory responses in the airways and lungs by restoring the lung damage by PM10D. It also regulated intestinal immunity and ameliorated the gut barrier function in the ileum. These results indicate the potential of L. paracasei ATG-E1 as an effective protective and therapeutic agent against airway inflammation and respiratory diseases.